PERPSEPSI ORANGTUA TERHADAP PERILAKU EGOSENTRIS ANAK USIA DINI - Kirey Kharisma Aulia, - (2021)
Egocentric behavior is a definite phenomenon experienced by every child in the preoperational stage. In this stage, there is a limitedness to the way children think because inability to understand situations and see the different perspectives or views of others. That matter, parents need to provide stimulation to their children. Before doing stimulation, parents have an egocentric view and a different way to deal with this periode and respond to any behaviors that arise during the egocentric behavior in early childhood. If the egocentric behavior is not addressed and managed by parents, it is worried that problems will grow in further development. This study uses a qualitative approach with a case study method through semi-structured interviews with 2 parents which means 2 fathers and 2 mothers who have early childhood especially 3-4 years. Data analysis using Miles & Huberman Inductive nature means that the data obtained and developed into a hypothesis through data reduction, data display, and drawing conclusions. The research findings show that parents' views on egocentric behavior in early childhood especially 3-4 years old are not always bad, the views of fathers and mothers regarding behavior that appears and stands out in children are different. Egocentric behavior is a learning process, self-maturation, and emotional control that will affect other developments. The importance of being addressed early on so that the behavior that appears does not lead to negative things in further development. The variety of ways in which parents deal with their child's egocentric behavior that arises makes it important for mothers and fathers to work together and become role models, building closeness between parents and children to better understand the situation and condition of the child.